مساهمة الألياف الفولاذية في زيادة قوة القص لجوائز مصنعة من البيتون ذاتي التوضع عالي المقاومة - تريكية علي; زلوخ فادي (Latakia University Journal -Engineering Sciences Series, 2019)
This research gives an experimental study of the effect of steel fibers on shear strength of the high- strength self-compacting concrete beams under of the continuous static loading effect . A mixture of self- compacting concrete was designed with two strength to (25-60) MPa and steel fibers were added ratio (0%,0.4%,0.8%,1.2%),ten beams were designed for each strength, five beams were tested on the shear as slender beams with shear field ratio(a/d= 3.3), and the other five beams were tested as deep beams with shear field ratio (a/d = 2.2). The test results showed that the addition of steel fibers to the self- compacting concrete mix resulted in increased shear strength in slender concrete beams with strength (25 MPa) between (18% - 100.9%) as well as increased shear strength in slender concrete beams with strength (60 MPa) between (48.4% - 51.9%) when the percentage ratio of steel fibers increased from (0.4% - 0.8%) but this increase decreased to (36.1%) when the percentage of steel fibers ratio (1.2%) , for deep concrete beams with strength (25 MPa), shear strength increased between ( 21% - 99.2% ) when the ratio of steel fibers increased from (0.4% - 0.8%), but this increase decreased to (74.5%) at the ratio of steel fibers (1.2%), With regard to deep beams with strength (60 MPa), shear strength increased by increasing the ratio of steel fibers between (17.5% - 73.6%), The results also showed that steel fibers can replace the stirrups in bearing shear strength at( 0.8%) for slender beams, and deep beams. يقدم هذا البحث دراسة تجريبية لتأثير الألياف الفولاذية على قوة القص للجوائز المصنعة من البيتون ذاتي التوضع عالي المقاومة تحت تأثير التحميل الستاتيكي المستمر. تم تصميــــم خلطـــــــــة بيتونيـــــة ذاتيــــــــــــــة التوضع بمقاومتيــــــن MPa ( 25 – 60 ) وإضافـــــــــــــــة الياف فولاذيـــــة إليها بنسب ( 0 %, 0.4% , 0.8% , 1.2 % ) وتم تحضير عشرة جوائز لكل مقاومة، واختبار خمسة منها على القص كجوائز نحيفة بنسبة مجال القص ( a/d = 3.3 ) والخمسة الباقية كجوائز عميقة بنسبة ( ( a/d = 2.2 . اظهرت نتائج الاختبار أن إضافة الالياف الفولاذيـــــة ادى إلى زيادة قوة القص في الجوائز البيتونية النحيفة ذات المقاومة (25 MPa ) بين ( 18 % و 100.9 % ) وكذلك زادت قوة القص في الجوائز النحيفــة ذات المقاومــة( 60 MPa ) بين ( 48.4 % و 51.9 % ) عند زيادة نسب الألياف من ( 0.4 % - 0.8 % ) لكنها انخفضت إلى (36.1 % ) عند نســـــــــبــــــة الألياف ( 1.2 % ) , وبالنســــبــــــة للجــــــوائز العميقـــــــــة ذات المقاومــــــــــــــــة (25 MPa) زادت قوة القــــــــص بيـــــــن ( 21 % و 99.2 % ) عند زيادة نسبة الألياف الفولاذية من ( 0.4 % - 0.8 % ) ولكنها انخفضت إلى ( 74.5 %) عند نسبة حجم الألياف ( 1.2% ) وفيما يتعلق بالجوائز العميقة ذات المقاومة (60 MPa) زادت قوة القص بزيادة نسب الألياف وتراوحت هذه الزيادة بين (17.5% - 73.6% ) , وكذلك بينت النتائج بأنه يمكن للألياف الفولاذيــة أن تحل مكان الأساور في تحمل قوة القص عند النسبة ( 0.8 % ) للجوائز النحيفة والعميقة.